Thrombolysis in posterior circulation stroke: stroke subtypes and patterns, complications and outcome - Förster, Alex; Gass, Achim; Kern, Rolf; Griebe, Martin; Hennerici, Michael G.; Szabo, Kristina (Cerebrovascular diseases, 2011)
Background: Patients with posterior circulation stroke (PCS) were underrepresented in or even excluded from the large clinical trials investigating acute therapy with thrombolysis. Therefore, the knowledge about potential benefits and risks of thrombolysis in PCS is sparse. Methods: From July 2004 until June 2007, 237 stroke patients were treated with thrombolysis within 3 h after onset of symptoms in our stroke unit. Baseline characteristics, etiology, CT/MRI stroke patterns, clinical outcome, and complications of patients with PCS were compared to those with anterior circulation stroke (ACS). Results: There were 30 patients in the PCS group; 198 had ACS. In the PCS group, less patients had a history of prior stroke (0/30 vs. 31/198 (15.7%), p = 0.02) and less were treated with platelet inhibitors (6/30 (20.0%) vs. 83/198 (41.9%), p = 0.02). Onset to treatment time was higher in the PCS group (156.2 ± 23.2 vs. 141.1 ± 30.7, p = 0.01). Small vessel disease occurred more often in PCS patients (10/30 (33.3%) vs. 12/198 (6.1%), p < 0.001), whereas stroke of undetermined cause was less frequent (5/30 (16.7%) vs. 75/198 (37.9%), p = 0.02). Correspondingly, PCS patients had more lacunar (13/30 (43.3%) vs. 15/198 (7.3%), p < 0.001) strokes on CT/MRI. Patients with PCS had significantly lower median NIHSS scores after 2 and 24 h, whereas the median NIHSS and mRS scores at discharge as well as the mRS score at the 3-month follow-up, although still lower, did not differ significantly between both groups. Outcome was similar with regard to complications and mortality. Conclusions: Patients with PCS have a higher rate of small vessel disease and lacunar stroke. In terms of potential benefits and risks of thrombolysis, we could demonstrate no significant differences between PCS and ACS. Acute PCS patients should be diagnosed and treated with the same elaborateness as ACS patients.
Gesehen am 15.05.2023